2004
DOI: 10.1093/bja/aeh257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperbaric and plain ropivacaine 15 mg in spinal anaesthesia for lower limb surgery

Abstract: In comparison with the plain solution, 15 mg of intrathecal hyperbaric ropivacaine produced a faster onset, greater success rate of analgesia at the level of T(10) dermatome, and faster recovery of the block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 10 publications
(10 reference statements)
6
53
0
1
Order By: Relevance
“…Difference in the onset of motor blockade in both groups was also found to be statistically significant (P <0.05). These findings of present study are similar with the findings stated by Van [17][18][19][20][21][22] The duration of sensory blockade was defined as time elapsed between injection of study drug and return of the pin prick sensation whereas duration of motor blockade was defined as time between drug injections to complete return of motor power with movement of all lower limb joints. It was found that longer duration of sensory and motor blockade in bupivacaine group as against in ropivacaine group and difference was statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Difference in the onset of motor blockade in both groups was also found to be statistically significant (P <0.05). These findings of present study are similar with the findings stated by Van [17][18][19][20][21][22] The duration of sensory blockade was defined as time elapsed between injection of study drug and return of the pin prick sensation whereas duration of motor blockade was defined as time between drug injections to complete return of motor power with movement of all lower limb joints. It was found that longer duration of sensory and motor blockade in bupivacaine group as against in ropivacaine group and difference was statistically significant (P <0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Usually, glucose-free solutions are marginally hypobaric and have been found previously to be 'unpredictably' (Logan et al, 1986) spread. Many studies (Fettes et al, 2005;Whiteside et al, 2001;Kallio et al, 2004) showed that hyperbaric solutions of local anesthetics for spinal anesthesia produce a more rapid spread to a higher median level and less variation in maximum sensory and motor block and might enable a smaller dose to be used compared with plain solutions. Especially in pregnant women, the width of the hips is usually larger than the shoulders which result in a head-down tilt when lying in the lateral position (Khaw et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Khaw KS et al, [2]; Gupta R et al, [8]; Kallio H et al, [10]; Fettes PD et al, [11] observed that median time taken for complete regression of sensory and motor blockade were significantly shorter in hyperbaric group than in isobaric group.…”
Section: Discussionmentioning
confidence: 99%